Hubungan Komposisi Tubuh dan Kualitas Tidur dengan VO2max pada Atlet Remaja di SMAN Olahraga Sidoarjo dan SMAN 1 Sewon: The Relationship of Body Composition and Sleep Quality with VO2max in Adolescent Athletes at Sidoarjo Sports High School and Sewon 1 High School - Mutiara, Fathirani; Muslichah, Rahadyana; Penggalih, Mirza Hapsari Sakti Titis (Amerta Nutrition, 2024)
Background: Body composition and sleep quality are body components that need to be considered in adolescent athletes. Both components can affect the level of maximum oxygen volume (VO2max) and become factors in increasing physical performance in adolescent athletes. Objectives: To determine the relationship between body composition and sleep quality with VO2max in adolescent athletes at Sidoarjo Sports High School and Sewon 1 High School. Methods: This cross-sectional study was conducted with 106 athletes selected by purposive sampling. Quantitative data were obtained using Bioelectrical Impedance Analysis (BIA), the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and the Multistage Fitness Test. The statistical tests used were the Pearson Product Moment and Spearman Rank. Results: There was a significant negative relationship between the percentage of fat mass and VO2max in both combined subjects (r=-0.669, p-value<0.001), male (r=-0.295, p-value=0.026), and female (r=-0.486, p-value<0.001). There was a significant positive relationship between the percentage of muscle mass and VO2max both with combined subjects (r=0.628, p-value<0.001) and women (r=0.492, p-value<0.001). There was no significant relationship between sleep quality and VO2max but there was a relationship in the components of sleep quality, namely subjective sleep quality (r=-0.34, p-value=0.01) and sleep efficiency (r=-0.29, p-value=0.03) with VO2max in female athletes. Conclusions: Adolescent athletes with a low percentage of fat mass tend to have high VO2max, while adolescent athletes with a low percentage of muscle mass tend to also have low VO2max. There was no significant relationship between sleep quality and VO2max.